Analysis of IT service management in the cloud: benefits and risks of its implementation - García Charcape, Angello Paul (2023)
This analysis examines the benefits and risks of managing IT services in the cloud. Implementing cloud services offers advantages such as cost reduction and flexibility, but it also presents risks related to data security, privacy and vendor lock-in. The best practices such as careful selection of providers, the implementation of security and privacy measures, continuous monitoring of services, and the management of a disaster backup plan are highlighted. While the adoption of cloud services offers significant benefits for organizations, it is crucial to address risks through proper management. The research uses exploratory and descriptive methods, including a systematic literature review. Fifteen relevant articles that analyze the benefits and risks of the cloud were identified, as well as solutions to mitigate attacks and optimize cloud services. These studies highlight the projected growth of the cloud services market, the benefits, as well as the associated security and privacy risks. It is essential to properly assess and manage both benefits and risks when implementing IT services in the cloud.